Colonic motor abnormalities in slow transit constipation defined by high resolution, fibre‐optic manometry. Issue 3 (3rd January 2015) - Dinning, P. G.; Wiklendt, L.; Maslen, L.; Patton, V.; Lewis, H.; Arkwright, J. W.; Wattchow, D. A.; Lubowski, D. Z.; Costa, M.; Bampton, P. A.
Abstract: Background: Slow transit constipation (STC) is associated with colonic motor abnormalities. The underlying cause(s) of the abnormalities remain poorly defined. In health, utilizing high resolution fiber‐optic manometry, we have described a distal colonic propagating motor pattern with a slow wave frequency of 2–6 cycles per minute (cpm). A high calorie meal caused a rapid and significant increase in this activity, suggesting the intrinsic slow wave activity could be mediated by extrinsic neural input. Utilizing the same protocol our aim was to characterize colonic meal response STC patients. Methods: A fiber‐optic manometry catheter (72 sensors at 1 cm intervals) was colonoscopically placed with the tip clipped at the ascending or transverse colon, in 14 patients with scintigraphically confirmed STC. Manometric recordings were taken, for 2 h pre and post a 700 kCal meal. Data were compared to 12 healthy adults. Key Results: Prior to and/or after the meal the cyclic propagating motor pattern was identified in 13 of 14 patients. However, the meal, did not increase the cyclic motor pattern (preprandial 7.4 ± 7.6 vs postprandial 8.3 ± 4.5 per/2 h), this is in contrast to the dramatic increase observed in health (8.3 ± 13.3 vs 59.1 ± 89.0 per/2 h; p  < 0.001). Conclusions & Inferences: In patients with STC a meal fails to induce the normal increase in the distal colonic cyclic propagating motor patterns. We propose that these data may indicate that the normal extrinsic parasympathetic inputs to the colon are attenuated in these patients. Abstract : Utilizing fiber‐optic, high resolution colonic manometry, in patients with slow transit constipation, we have defined the colonic motor abnormalities in response to a high calorie meal. We propose a hypothesis that a possible neuropathy in the extrinsic parasympathetic inputs to the colon of patients with slow transit constipation may exist.